IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH ENGLISH SONG - Liva, Clara; Sutapa Y, Y. Gatot; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of the research is to improve students’ speaking ability through English Song. The research was conducted in order to solve the problem encountered in the classroom; the students are not interested in speaking English. To collect the data, the writer chose speaking test, observation checklist, and field notes. The writer and research collaborator apply them to know the improvement of students’ speaking ability through English Song in each cycle. Through field notes, the writer reflected students’ performance in a meeting for the next cycle. The research took 3 cycles. The subjects of this research were 38 eighth grade class G students of SMPN 2 Sintang in academic year 2013/2014. On first cycle, 5.3 % students scored from 80–100 (good to excellent), 34.2 % students scored from 60–79 (average to good), 13.2% students scored from 50–59 (poor to average), and 47.4% students scored below 50 (poor). On second cycle, 21.1% students scored from 80–100 (good to excellent), 26.3 % students scored from 60-79 (average to good), 18.4 % students scored from 50 – 59 (poor to average), and 34.2 % students scored below 50 (poor). On third cycle, 44.7 % students scored from 80–100 (good to excellent), 39.5 % students scored from 60–79 (average to good), 15.8 % students scored from 50–59 (poor average), and 0 % students scored below 50 (poor). After analyzing students’ score, the writer concluded that students’ speaking ability had been improved through English song. Keywords: Speaking ability, English song Abstrak: Tujuan penelitian ini adalah meningkatkan kemampuan berbicara siswa melalui lagu berbahasa Inggris. Penelitian dilakukan dengan tujuan mengatasi masalah yang ditemui dikelas: siswa tidak tertarik berbicara bahasa Inggris. Untuk pengumpulan data, penulis memilih tes berbicara, ceklis untuk observasi, dan catatan lapangan. Penulis dan kolaborator menerapkannya untuk mengetahui peningkatan kemampuan berbicara siswa melalui lagu berbahasa Inggris di tiap siklus. Melalui catatan lapangan, penulis menggambarkan penampilan siswa dalam sebuah pertemuan untuk siklus berikutnya. Penelitian memerlukan 3 siklus. Subyek penelitian ini adalah 38 siswa tingkat 8 kelas G di SMPN 2 Sintang tahun ajaran 2013/2014. Pada siklus pertama, 5.3 % siswa mendapat nilai dari 80–100 (baik ke sangat baik), 34.2 % siswa mendapat nilai dari 60–79 (biasa ke baik), 13.2% siswa mendapat nilai dari 50–59 (buruk ke biasa), dan 47.4% siswa mendapat nilai dibawah 50 (buruk). Pada siklus kedua, 21.1% siswa mendapat nilai dari 80–100 (baik ke sangat baik), 26.3 % siswa mendapat nilai dari 60-79 (biasa ke baik), 18.4 % siswa mendapat nilai dari 50 – 59 (buruk ke biasa), dan 34.2 % siswa mendapat nilai dibawah 50 (buruk). Pada siklus ketiga, 44.7 % siswa mendapat nilai dari 80–100 (baik ke sangat baik), 39.5 % siswa mendapat nilai dari 60–79 (biasa ke baik), 15.8 % siswa mendapat nilai dari 50–59 (buruk ke biasa), dan 0 % siswa mendapat nilai dibawah 50 (buruk). Setelah menganalisa nilai siswa, penulis menyimpulkan bahwa kemampuan berbicara siswa telah meningkat menggunakan lagu berbahasa Inggris Kata Kunci: Kemampuan berbicara, lagu berbahasa Inggris